Evaluation of the diagnostic yield of lung cancer on various Bronchoscopic modalities - Shahi, Rejina; Bhatta, Narendra; Verma, Avatar; Upreti, Augraj; Gurung, Kum Bahadur; Chaudhary, Sabnam; Dhakal, Nishchal; Mishra, Deebya Raj (Nepalese Respiratory Journal, 2023)
Background: The application of cytological techniques in identifying malignant respiratory tract lesions has been widely praised as a significant achievement. Flexible fiberoptic bronchoscopy has greatly transformed respiratory cytology, making procedures such as bronchial brushings, broncho-alveolar lavage, and bronchial forceps biopsy more convenient, accessible, and popular. Methodology: All the suspected cases of lung cancer from 1st Jan, 2020 - 31st Dec, 2022 fulfilling inclusion criteria who have undergone flexible bronchoscopy in our center have been analyzed and enrolled in the study. Results: Out of 90 patients, 85 were found to be malignant. Squamous cell carcinoma was the most common carcinoma (31.1%) followed by adenocarcinoma (26.7%), non-small Cell Lung Carcinoma (17.8%) and small cell carcinoma (12.2%), majority of the cases were of 6-7th decade of life and were smoker. Sensitivities of Bronchoalveolar Lavage (BAL), Bronchial brush, Endobronchial forceps Biopsy (EBB), Transbronchial Lung Biopsy (TBLB) and Transbronchial Needle Aspiration (TBNA) were found to be 32%, 87%, 83%, 55% and 69% respectively. Diagnostic accuracy of BAL, bronchial brush, EBB, TBLB and TBNA were found to be 36%, 87%, 83%, 55% and 61% respectively. Conclusion: With a greater sensitivity (87%) and diagnostic accuracy (87%), bronchial brushing shows great promise as a convenient cytological technique suitable for screening ambiguous cases and early detection of lung cancer, as it saves the time required for processing biopsy samples.